Adenosine-to-inosine RNA editing contributes to type I interferon responses in systemic sclerosis. Issue 125 (December 2021) - Vlachogiannis, Nikolaos I.; Tual-Chalot, Simon; Zormpas, Eleftherios; Bonini, Francesca; Ntouros, Panagiotis A.; Pappa, Maria; Bournia, Vasiliki-Kalliopi; Tektonidou, Maria G.; Souliotis, Vassilis L.; Mavragani, Clio P.; Stamatelopoulos, Kimon; Gatsiou, Aikaterini; et al.
Abstract: Objective: Adenosine deaminase acting on RNA-1 (ADAR1) enzyme is a type I interferon (IFN)-stimulated gene (ISG) catalyzing the deamination of adenosine-to-inosine, a process called A-to-I RNA editing. A-to-I RNA editing takes place mainly in Alu elements comprising a primate-specific level of post-transcriptional gene regulation. Whether RNA editing is involved in type I IFN responses in systemic sclerosis (SSc) patients remains unknown. Methods: ISG expression was quantified in skin biopsies and peripheral blood mononuclear cells derived from SSc patients and healthy subjects. A-to-I RNA editing was examined in the ADAR1-target cathepsin S ( CTSS ) by an RNA editing assay. The effect of ADAR1 on interferon-α/β-induced CTSS expression was assessed in human endothelial cells in vitro . Results: Increased expression levels of the RNA editor ADAR1, and specifically the long ADAR1p150 isoform, and its target CTSS are strongly associated with type I IFN signature in skin biopsies and peripheral blood derived from SSc patients. Notably, IFN-α/β-treated human endothelial cells show 8-10-fold increased ADAR1p150 and 23-35-fold increased CTSS expression, while silencing of ADAR1 reduces CTSS expression by 60-70%. In SSc patients, increased RNA editing rate of individual adenosines located in CTSS 3 ′ UTR Alu elements is associated with higher CTSS expression (r = 0.36–0.6, P < 0.05 for all). Similar findings were obtained in subjects with activated type I IFN responses including SLE patients or healthy subjects after influenza vaccination. Conclusion: ADAR1p150-mediated A-to-I RNA editing is critically involved in type I IFN responses highlighting the importance of post-transcriptional regulation of proinflammatory gene expression in systemic autoimmunity, including SSc. Graphical abstract: Increased type I interferon (IFN-α/β) in patients with systemic sclerosis (SSc), systemic lupus erythematosus (SLE) or healthy subjects after influenza vaccination leads to increased expression of the ADAR1p150 enzyme. Increased ADAR1p150 in turn leads to increased adenosine-to-inosine (A-to-I) RNA editing of Alu elements. We were able to detect a 'hotspot' region within AluSx + in cathepsin S 3 ′ untranslated region, characterized by the presence of 13 A-to-I RNA editing events within 50 bps and of 5 binding motifs of the stabilizing single-stranded RNA-binding protein HuR. A-to-I RNA editing unwinds the local double-stranded RNA structure into a more single-stranded conformation, thus revealing HuR binding motifs. Increased A-to-I RNA editing rate of the 'hotspot' region in SSc and SLE patients, or after acute induction of a systemic type I IFN response, may thus facilitate recruitment of the stabilizing single stranded RNA-binding protein HuR to its target motifs, ultimately increasing CTSS transcript stability and expression. Image 1 Highlights: Adenosine deaminase acting on RNA-1 (ADAR1) is an interferon-stimulated gene. ADAR1p150 enzyme isoform is the main RNA editor in systemic sclerosis (SSc). Increased ADAR1p150 and cathepsin S expression levels are associated with type I interferon in patients with SSc. Increased adenosine-to-inosine RNA editing contributes to cathepsin S expression in patients with SSc. Similar findings are observed also in SLE or after acute induction of type IFN response by influenza vaccination.